Synthesis of fatty acid methyl ester from the transesterification of high- and low-acid-content crude palm oil (Elaeis guineensis) and karanj oil (Pongamia pinnata) over a calcium–lanthanum–aluminum mixed-oxides catalyst. (August 2016) - Syamsuddin, Y.; Murat, M.N.; Hameed, B.H.
Highlights: Transesterification of vegetable oil with different acid contents into FAME. Best conditions from the reaction of vegetable oils with different acid contents. The synthesized catalyst was feasible for high- and low-acid-content oil. The properties of both products confirmed the standard requirements. Abstract: The synthesis of fatty acid methyl ester (FAME) from the high- and low-acid-content feedstock of crude palm oil (CPO) and karanj oil (KO) was conducted over CaO–La2 O3 –Al2 O3 mixed-oxide catalyst. Various reaction parameters were investigated using a batch reactor to identify the best reaction condition that results in the highest FAME yield for each type of oil. The transesterification of CPO resulted in a 97.81% FAME yield with the process conditions of 170 °C reaction temperature, 15:1 DMC-to-CPO molar ratio, 180 min reaction time, and 10 wt.% catalyst loading. The transesterification of KO resulted in a 96.77% FAME yield with the conditions of 150 °C reaction temperature, 9:1 DMC-to-KO molar ratio, 180 min reaction time, and 5 wt.% catalyst loading. The properties of both products met the ASTMD6751 and EN 14214 standard requirements. The above results showed that the CaO–La2 O3 –Al2 O3 mixed-oxide catalyst was suitable for high- and low-acid-content vegetable oil.